Involvement of genes of genome maintenance in the regulation of phase variation frequencies in Neisseria meningitidis. - Martin, P; Sun, L; Hood, D; Moxon, E (2004)
In Neisseria meningitidis, the reversible expression of surface antigens, i.e. phase variation, results from changes within repeated simple sequence motifs located in coding or promoter regions of the genes involved in their biosynthesis. The mutation rates of these simple sequences, which have a major influence on the generation of phenotypic diversity, can affect the fitness of the population. The aim of the present study was to investigate the involvement of genetic factors involved (mutS and dam) and not yet analysed (drg and dinB) in the regulation of phase variation frequencies of genes associated with a variety of repeat tracts. The frequency of frameshifts occurring in the polycytidine (polyC) tracts associated with siaD, spr and lgtG and in the tetranucleotide (TAAA) repeat tract associated with nadA was determined by colony immunoblotting or using the lacZ gene as a reporter. Inactivation of mutS increased the frequency of phase variation of genes presenting homopolymeric tracts of diverse length. Overexpression of dinB enhanced the instability of the homopolymeric tract associated with siaD. Investigation of the dam locus in a population of genetically distinct N. meningitidis strains revealed that 27 % of strains associated with invasive disease contained the dam gene. In all strains where a Dam function was absent, the drg gene had been inserted into the dam locus. Disruption of dam and drg in strains representative of each genotype, i.e. dam(+)/drg and dam/drg(+), did not modify phase variation frequencies. In contrast to the effects of certain genes on homopolymeric tracts, none of the genetic factors investigated affected the stability of tetranucleotide repeat tracts.